2022
DOI: 10.3390/w14030490
|View full text |Cite
|
Sign up to set email alerts
|

Daily Streamflow Forecasting Based on the Hybrid Particle Swarm Optimization and Long Short-Term Memory Model in the Orontes Basin

Abstract: Water, a renewable but limited resource, is vital for all living creatures. Increasing demand makes the sustainability of water resources crucial. River flow management, one of the key drivers of sustainability, will be vital to protect communities from the worst impacts on the environment. Modelling and estimating river flow in the hydrological process is crucial in terms of effective planning, management, and sustainable use of water resources. Therefore, in this study, a hybrid approach integrating long sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Khan et al, 2016), which makes it appealing for use in a variety of domains, such as water demand prediction (Ömer Faruk, 2010;Zubaidi, Abdulkareem et al, 2020;Zubaidi, Dooley et al, 2018;, streamflow forecasting (Apaydin et al, 2021;F.F. Li et al, 2021;Gunathilake et al, 2021;Huang et al, 2021;Kilinc, 2022;Kilinc & Haznedar, 2022;Kim et al, 2022;Niu & Feng, 2021;Rahimzad et al, 2021), water quality predictions (Abba et al, 2017;W. Li et al, 2020;Sami et al, 2021;Stamenković, 2021;Tahraoui et al, 2021;Y.-F. Zhang et al, 2020), and drought prediction (Adamowski et al, 2012;Ahmadi et al, 2021;Dikshit et al, 2020;M.M.H.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Khan et al, 2016), which makes it appealing for use in a variety of domains, such as water demand prediction (Ömer Faruk, 2010;Zubaidi, Abdulkareem et al, 2020;Zubaidi, Dooley et al, 2018;, streamflow forecasting (Apaydin et al, 2021;F.F. Li et al, 2021;Gunathilake et al, 2021;Huang et al, 2021;Kilinc, 2022;Kilinc & Haznedar, 2022;Kim et al, 2022;Niu & Feng, 2021;Rahimzad et al, 2021), water quality predictions (Abba et al, 2017;W. Li et al, 2020;Sami et al, 2021;Stamenković, 2021;Tahraoui et al, 2021;Y.-F. Zhang et al, 2020), and drought prediction (Adamowski et al, 2012;Ahmadi et al, 2021;Dikshit et al, 2020;M.M.H.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Machine learning (ML) techniques can learn from past experience (data) and create new (mathematical) models that can be applied to new data. ML has been applied in many areas of the hydrology fields, for example, stream flow (Kilinc, 2022;Kilinc & Haznedar, 2022). There are different types of ML used in the field of water level prediction, such as artificial neuro-fuzzy inference system (ANFIS), artificial neural network (ANN), support vector regression (SVR), and a variety of hybrid models (Çimen & Kisi, 2009;B.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison results showed that all models have excellent prediction effects. Moreover, in this study, two important parameters, the number of hidden-layer nodes and the learning rate of the LSTM model, were optimized by the PSO algorithm [57], and the optimized BiLSTM model was compared with the benchmark LSTM model. The results showed that the PSO algorithm-based model parameter optimization and the BiLSTM structure can improve the prediction performance of the benchmark LSTM model.…”
Section: Prospect Of Hydrologic Application Of Pso-lstm and Bilstm Mo...mentioning
confidence: 99%
“…The traditional LSTM model will show obvious instability in the training process, and even the gradient will disappear. [48][49][50] Therefore, this study proposes PSO-CS optimization algorithm to iteratively optimize the LSTM model and find the optimal parameters of the model. That is, the PSO-CS algorithm is used to optimize the two key parameters of LSTM model (the number of neurons m and the learning rate lr).…”
Section: Long Short-term Memory Modelmentioning
confidence: 99%